Active tourism and sport: outlining a line of research in social sciences - Muñoz-Sánchez, Víctor Manuel; Pérez-Flores, Antonio Manuel; Jordi-Sánchez, Mario (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Tourism is one of the most important elements in relation to the vectors of social change. The proposed objective is descriptive-bibliometric analysis of active tourism and its relationship to sporting activities through a study of the academic output in Scopus. The conclusions profile the research interests, themes, topics and distinctive elements of papers addressing this area of research, showing that there is a wide range of publications on the relationship between active tourism and sport, considering various sporting activities as tourism offerings in a large variety of geographic locations.